Efficacy of Calcium Hydroxylapatite Filler versus Hyaluronic Acid Filler in Hand Augmentation - Sattler, G.; Walker, T.; Buxmeyer, B.; Biwer, B. (Aktuelle Dermatologie, 2014)
Purpose: This study compared long-term safety and efficacy of the dermal fillers calcium hydroxylapatite versus hyaluronic acid in hand augmentation in a head-to-head design. Patients and methods: The partially blinded, randomized study was conducted from July 2012 to November 2013. Subjects aged 45 – 65 years presenting for hand rejuvenation with a score of 3 or 4 on the validated Merz 5-point hand grading scale were included. Subjects were injected in a randomized manner with calcium hydroxylapatite (Radiesse®) in the one hand and hyaluronic acid (Juvéderm® Ultra 4) in the other hand. Observation time per patient was 12 months. Data were assessed at baseline, week 4 – 6, and months 3, 9, and 12. The primary efficacy variable was changes on the hand grading scale. Other assessments included cosmetic result, global esthetic improvement, patient and physician satisfaction, and procedural pain. Adverse events were documented at each follow-up visit. Results: Thirty-seven female patients participated in the study. Both dermal fillers led to significant improvement from baseline on the hand grading scale. 13 patients required a touch-up for both hands, 3 more patients required a touch-up in the hyaluronic acid filler-treated hand only. After 12 months, the treatment effect was still visible for both fillers. The cosmetic result was rated very good or good and global esthetic improvement was concurrently confirmed for both dermal fillers by the blinded and the unblinded physician. There was no difference in terms of satisfaction with the cosmetic result and procedural pain. In total, 11 transient adverse events related to the injection with calcium hydroxylapatite were documented in 6 patients.Conclusion: Calcium hydroxylapatite and hyaluronic acid are equally suited for achieving long-term results in hand augmentation. Calcium hydroxylapatite was more effective in attaining short-term results with a smaller injection volume. Both dermal fillers were well tolerated and did not induce any serious or unanticipated adverse events.